2021
DOI: 10.1021/acsami.1c00083
|View full text |Cite
|
Sign up to set email alerts
|

Reusable MoS2-Modified Antibacterial Fabrics with Photothermal Disinfection Properties for Repurposing of Personal Protective Masks

Abstract: The current pandemic caused by SARS-CoV-2 has seen a widespread use of personal protective equipment, especially face masks. This has created the need to develop better and reusable protective masks with built-in antimicrobial, self-cleaning, and aerosol filtration properties to prevent the transmission of air-borne pathogens such as the coronaviruses. Herein, molybdenum disulfide (MoS 2 ) nanosheets are used to prepare modified polycotton fabrics having excellent antibacterial activity and photothermal proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 44 publications
1
110
0
Order By: Relevance
“… ( El-Atab et al, 2020 ; Kumar et al, 2021 , Kumar et al, 2020 ; Lee et al, 2020 ; Lin et al, 2021 ; Wang et al, 2020 ; Yang et al, 2020 ; Zhong et al, 2020 ) 8 Self-cleaning Self-disinfecting Self-sanitizing Self-decontaminating Photo-sterilize, thermal-sterilize Applying photo (UV) or thermal disinfecting procedure to introduce self-sterilization and enable reusability. ( Banerjee et al, 2021 ; Kumar et al, 2021 , Kumar et al, 2020 ; Lin et al, 2021 ; Zhong et al, 2020 ) 9 Fluid repellent and superhydrophobicity Increases the effective use time in different conditions specially for HCWs (anti-splash, …) ( El-Atab et al, 2020 ; Lin et al, 2021 ; Zhong et al, 2020 ) 10 Special features (smart) Uses special materials or designs to increase the performance and appearance of face masks. The transparent look can help avoid the threatening appearance of the mask and can allow lip reading for people with mutism or hearing impairment.…”
Section: Multifunctional Surgical Face Masksmentioning
confidence: 99%
See 1 more Smart Citation
“… ( El-Atab et al, 2020 ; Kumar et al, 2021 , Kumar et al, 2020 ; Lee et al, 2020 ; Lin et al, 2021 ; Wang et al, 2020 ; Yang et al, 2020 ; Zhong et al, 2020 ) 8 Self-cleaning Self-disinfecting Self-sanitizing Self-decontaminating Photo-sterilize, thermal-sterilize Applying photo (UV) or thermal disinfecting procedure to introduce self-sterilization and enable reusability. ( Banerjee et al, 2021 ; Kumar et al, 2021 , Kumar et al, 2020 ; Lin et al, 2021 ; Zhong et al, 2020 ) 9 Fluid repellent and superhydrophobicity Increases the effective use time in different conditions specially for HCWs (anti-splash, …) ( El-Atab et al, 2020 ; Lin et al, 2021 ; Zhong et al, 2020 ) 10 Special features (smart) Uses special materials or designs to increase the performance and appearance of face masks. The transparent look can help avoid the threatening appearance of the mask and can allow lip reading for people with mutism or hearing impairment.…”
Section: Multifunctional Surgical Face Masksmentioning
confidence: 99%
“…5 Multifunctional surgical face masks. a) Anti-influenza multilayer containing copper oxide face masks with corresponding SEM and XPS analysis ( Borkow et al, 2010 ), b) reusable and recyclable graphene-coated superhydrophobic, self-cleaning and photothermal face masks ( Zhong et al, 2020 ), c) reusable MoS 2 -modified durable antibacterial and photothermal self-disinfection face masks ( Kumar et al, 2021 ), d) reusable copper nanoparticles (CuNPs) antiviral and photo-thermal self-disinfecting face masks ( Kumar et al, 2020 ), e) multifunctional face masks to protect people from PM pollutants and simultaneously achieve personal thermal comfort ( Yang et al, 2017 ), f) skin temperature when covered with multifunctional face masks and two commercial face masks ( Yang et al, 2017 ), g) filtration efficiency of a new KN95 mask, washed and dried mask, and recharged mask for 60 min. Decay of the efficiency of the recharged mask over the course of a day ( Hossain et al, 2020 ), h) multifunctional mask by using BaTiO3@PU/PSA membrane achieved the high capture efficiency, low pressure drop, good mechanical property, sufficient flexibility, high thermal stability, favorable flame-retardancy as well as superior chemical resistance against acid and alkali ( Yang et al, 2020 ).…”
Section: Multifunctional Surgical Face Masksmentioning
confidence: 99%
“…The NiFe formed onto SNF caused at least three pronounced alterations on the NF properties: surface area (increased from 5.35 m 2 g −1 for pure SNF to 40.05 m 2 g −1 NiFe@SNM‐4), fast adsorption kinetics for methylene blue within 20 min, and oleophobic character showing an oil contact angle of 174°, whereas non‐measurable hydrophobicity is observed, which features are promising for oil/water separation membrane. [ 230 ] Other 2D materials, such as MoS 2 and rGO anchored on fibers by post‐modifications strategies were also explored recently for dye, [ 198 ] bacteria, [ 231 ] and metal remediation. [ 11 ]…”
Section: Applicationsmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) is a two-dimensional (2D)-layered material having exciting and unique properties and can be used in several different applications. Polycotton fabric can also be fabricated to impart antibacterial properties on their surfaces with 2D materials, as illustrated by Kumar et al 11 in their study. The authors reported that the MoS 2 -coated fabrics had excellent antibacterial activity against Gram-positive and Gram-negative bacteria and possessed photothermal properties when exposed to sunlight.…”
Section: Modified Polymer-based Ppementioning
confidence: 99%